Use of estradiol benzoate to induce ovulation in a short-term protocol for fixed-time AI in sheep - Castilho, Caliê; De Almeidav, Marcelo Ferreira; Giometti, Ines Cristina; Costa, Marcelo Zoccolaro; Filho, Luís Roberto Almeida Gabriel [UNESP]; De Cesare, Angelo Gardim (Universidade Estadual de Londrina, 2015)
The aim of this study was to test the hormonal protocol for fixed-time artificial insemination (TAI) with a progesterone vaginal device for six days applying equine chorionic gonadotropin (eCG) or estradiol benzoate (EB) as an ovulation inducer in ewes. On day 0(D0), the ewes (n=31) received a device containing 0.33 g of intravaginal progesterone (CIDR®) and were divided into three groups. The G-CT (control group) used CIDR for nine days and upon withdrawal of the progesterone, were administered prostaglandin F2 alpha (PGF2α) and eCG. In the eCG (G-eCG) group, CIDR was administered for six days, instead of nine as in the G-CT group, followed by PGF2a and eCG after progesterone withdrawal. In the EB (G-EB) group, CIDR was also administered for six days, but eCG was not applied, and EB was used to induce ovulation 24 hours after removing the CIDR and PGF2a application. TAI was realized in all groups 50 hours after CIDR withdrawal. The pregnancy rate in the G-eCG group (66.66%) was higher (p <0.05) than that in the G-EB group (11.11%). The short-term groups showed no difference (p>0.05) compared to the G-CT group (30%). It is possible to reduce the application time of the progesterone and use eCG for TAI in sheep; however, using EB resulted in a low ovulation rate in the sheep.
Keywords: Laparoscopy; Ovine CIDR; Ovulation; Serum progesterone